A Critical Analysis of the Relevance of Thucydides’ Trap in the Contemporary World - Singh, Sudhir Pratap (The Shivapuri Journal, 2026)
This article critically analyzes the relevance of Thucydides’ Trap in today’s context—the idea that war becomes likely when a rising power challenges an established one. The framework, derived from Thucydides’ account of the Peloponnesian War and later revived by Graham Allison, focuses on fear, honor, and interest as the forces that push great powers toward confrontation. But the modern world is a lot more complicated, and that complexity pushes back against the notion that conflict is inevitable. By comparing past and present cases, such as the smooth transition of power from Britain to the US and the deeply intertwined economic relationship between the U.S. and China, the article shows how nuclear deterrence, globalization, domestic politics, economic interdependence, and international institutions all make large-scale war less likely. The overall takeaway is that while the clash between rising and established power can’t be ruled out, it isn’t predetermined either. Thucydides’ Trap is better seen as a warning than a prediction, and it misses much of what keeps modern rivalries from turning violent. This article critically analyses the relevance of Thucydides’ Trap in today’s context-the idea that war becomes likely when a rising power challenges an established one. The framework, derived from Thucydides’ account of the Peloponnesian War and later revived by Graham Allison, focuses on fear, honor, and interest as the forces that push great powers toward confrontation. But the modern world is a lot more complicated, and that complexity pushes back against the notion that conflict is inevitable. By comparing past and present cases, such as the smooth transition of power from Britain to the US and the deeply intertwined economic relationship between the U.S. and China, the article shows how nuclear deterrence, globalization, domestic politics, economic interdependence, and international institutions all make large-scale war less likely. The overall takeaway is that while the clash between rising and established power can’t be ruled out, it isn’t predetermined either. Thucydides’ Trap is better seen as a warning than a prediction, and it misses much of what keeps modern rivalries from turning violent.